2014
DOI: 10.9755/ejfa.v26i8.18364
|View full text |Cite
|
Sign up to set email alerts
|

Plants and algae species: Promising renewable energy production source

Abstract: Rapid increase in fossil energy consumption has raised

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Table 2.10 outlines and compares the most critical system aspects of open raceway ponds and PBR microalgal growth system. (Brennan & Owende, 2010;Kumar & Jain, 2014;Rosello Sastre et al, 2007;Travieso et al, 2001;Vonshak & Richmond, 1988) Several studies concerning microalgal growth for biofuel production have found cultivation of microalgae in open raceway ponds (ORP) as the most cost effective method of producing microalgal biofuel (Amanor-Boadu et Colosi, 2012;Nanaki & Koroneos, 2012;Ogden, 2014;Pfromm et al, 2011;Sander & Murthy, 2010 (Quinn & Davis, 2015;Chisti, 2007).…”
Section: Pond Vs Pbrmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2.10 outlines and compares the most critical system aspects of open raceway ponds and PBR microalgal growth system. (Brennan & Owende, 2010;Kumar & Jain, 2014;Rosello Sastre et al, 2007;Travieso et al, 2001;Vonshak & Richmond, 1988) Several studies concerning microalgal growth for biofuel production have found cultivation of microalgae in open raceway ponds (ORP) as the most cost effective method of producing microalgal biofuel (Amanor-Boadu et Colosi, 2012;Nanaki & Koroneos, 2012;Ogden, 2014;Pfromm et al, 2011;Sander & Murthy, 2010 (Quinn & Davis, 2015;Chisti, 2007).…”
Section: Pond Vs Pbrmentioning
confidence: 99%
“…Either an acid or base catalyst is typically used to facilitate the transesterification process (Ahmad et al 2013;Kumar and Jain 2014;Xu et al 2006). Types of catalysis include sulfuric acid, hydrogen chloride and sodium hydroxide (Kumar & Jain, 2014). Table 1 in Liu et al…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…They are also able to utilize various types of nitrogen compounds and absorb heavy metals. As a consequent, many studies have been done to seek possibilities of microalgae as a source of foods [1], energy production [2], medicines [3], and other valuable products.…”
Section: Introductionmentioning
confidence: 99%